Deliberative Political Leaders: The Role of Policy Input in Political Leadership - Lees-Marshment, Jennifer (2016)
This article provides a fresh perspective on political leadership by demonstrating that government ministers take a deliberative approach to decision making. Getting behind the closed doors of government through 51 elite interviews in the UK, US, Australia, Canada and New Zealand, the article demonstrates that modern political leadership is much more collaborative than we usually see from media and public critique. Politicians are commonly perceived to be power-hungry autocratic, elite figures who once they have won power seek to implement their vision. But as previous research has noted, not only is formal power circumscribed by the media, public opinion, and unpredictability of government, more collaborative approaches to leadership are needed given the rise of wicked problems and citizens increasingly demand more say in government decisions and policy making. This article shows that politicians are responding to their challenging environment by accepting they do not know everything and cannot do everything by themselves, and moving towards a leadership style that incorporates public input. It puts forward a new model of Deliberative Political Leadership, where politicians consider input from inside and outside government from a diverse range of sources, evaluate the relative quality of such input, and integrate it into their deliberations on the best way forward before making their final decision. This rare insight into politician’s perspectives provides a refreshing view of governmental leadership in practice and new model for future research.